2015
DOI: 10.1002/psp.1969
|View full text |Cite
|
Sign up to set email alerts
|

Is the Tied Returnee Male or Female? The Trailing Spouse Thesis Reconsidered

Abstract: A common finding of 30-40 years of family migration studies worldwide is that such migration primarily benefits the careers of men in couples but generally damages the women's careers. Findings have recently become more nuanced as the research focus has broadened, hinting that families returning to one spouse's region of previous residence might deviate from this general observation of men as gainers. The present research demonstrates that when families migrate to regions where one spouse has previously lived,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 52 publications
(76 reference statements)
1
25
0
1
Order By: Relevance
“…The effects of the gender order are further reflected in professional mobility and expatriation patterns. Research in these areas has repeatedly pointed out that geographical mobility is primarily beneficial to the careers of men and often disadvantages the careers of women in a couple (Amcoff & Niedomysl, ; Känsälä et al, ; Valcour & Tolbert, ; Van der Klis & Mulder, ). Numerous studies have shown how the ‘distinct gender dynamics' (Jöns, ) that mobility displays, disadvantage women — both in terms of access to short‐term as well as long‐term mobility (e.g., Brandén, Bygren, & Gähler, ; Lee, Chua, Miska, & Stahl, ; Varma & Russell, ; Wheatley, ) — especially when they have children (Guillaume & Pochic, ; Waibel, Aevermann, & Rueger, ).…”
Section: The Gender Ordermentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of the gender order are further reflected in professional mobility and expatriation patterns. Research in these areas has repeatedly pointed out that geographical mobility is primarily beneficial to the careers of men and often disadvantages the careers of women in a couple (Amcoff & Niedomysl, ; Känsälä et al, ; Valcour & Tolbert, ; Van der Klis & Mulder, ). Numerous studies have shown how the ‘distinct gender dynamics' (Jöns, ) that mobility displays, disadvantage women — both in terms of access to short‐term as well as long‐term mobility (e.g., Brandén, Bygren, & Gähler, ; Lee, Chua, Miska, & Stahl, ; Varma & Russell, ; Wheatley, ) — especially when they have children (Guillaume & Pochic, ; Waibel, Aevermann, & Rueger, ).…”
Section: The Gender Ordermentioning
confidence: 99%
“…The crucial role of 'trailing spouses' for the overall success of an overseas assignment has long been established (e.g., Cole & Nesbeth, 2014;Collins & Bertone, 2017;Harvey, 1998;Konopaske et al, 2005;Lauring & Selmer, 2010;Mäkelä, Känsälä, & Suutari, 2011;McNulty, 2012), and difficulties of adjustment for 'trailing spouses' are widely acknowledged (e.g., Cole & Nesbeth, 2014;Collins & Bertone, 2017;Harvey, 1998;Mäkelä et al, 2011;McNulty, 2012;Shahnasarian, 1991). Thus, although, as Amcoff and Niedomysl (2015) maintain, 'trailing spouses' may 'perceive additional, non-monetary, gains accruing from moving' (p. 872), they still often experience numerous disadvantages in terms of their own career progress and mental health (e.g., Cole & Nesbeth, 2014;Collins & Bertone, 2017;Schnurr, Zayts, & Hopkins, 2016;Shahnasarian, 1991).…”
Section: The Gender Ordermentioning
confidence: 99%
“…(Amcoff & Niedomysl, ; Bell et al, ; Camara & Garcia‐Roman, ; Clark, Duque‐Calvache, & Palomares‐Linares, ; Johnston, Poulsen, & Forrest, ; Mberu & Mutua, ; Mezger Kveder & Beauchemin, ; Midouhas & Flouri, ; Snel, Faber, & Engbersen, ; Svensson, Lundholm, De Luna, & Malmberg, ; Wang, Guo, & Cheng, ; Wilson, ; Yang, Noah, & Shoff, )…”
Section: Assemblage Thinking and Population Geographyunclassified
“…Other research notes gender differences over the course of the life course (Green, 1997), at different stages of the actual decision-making process (Seavers, 1999), over time (Smits et al, 2003) and for different migration types (Bailey & Cooke, 1998;Amcoff & Niedomysl, 2015). Cooke and Bailey (1999) suggest that families in fact give greater weight to the female's employment in migration decision-making than is assumed by the human capital model, and Challiol and Mignonac (2005) claim that a couple's decision-making process is increasingly a search for compromise solutions with respect to both the professional and family roles within the couple.…”
Section: The Migration and Retirement Behaviour Of Couplesmentioning
confidence: 99%
“…Add to this change in employment status those affecting other life domains – the move to a rural location (residential domain) alongside possibly children having left home (family domain) – and it becomes important to ask if the post‐migration experiences of retired couples are gendered. This section of the paper seeks to contribute to calls from Smith () and Amcoff and Niedomysl () to study post‐move satisfaction levels and to respond to Halfacree and Rivera's (: 92) observation that ‘… migrants' subsequent lives in rural places [are] much less examined’.…”
Section: Introductionmentioning
confidence: 99%